Beyond Fomo: Examining Joy of Missing Out as a Mediating Mechanism Between Self-Compassion and Subjective Well-Being Among Emerging Adulthood - Caca Pria Mardiansyah; Nanda Audia Vrisaba (Journal of Psychological Perspective, 2026)
The increasing use of social media is associated with two experiences during emerging adulthood, namely creating opportunities for social connectedness while generating psychological pressure, particularly related to Fear of Missing Out. Joy of Missing Out (JoMO) was introduced as a more adaptive orientation toward social media engagement. This study aimed to examine the role of JoMO as a mediator in the relationship between self-compassion and subjective well-being among social media users during emerging adulthood using a quantitative approach with purposive sampling involving 570 participants aged 18–29 years, predominantly female and students. Mediation analysis was conducted using Jamovi with a bootstrapping procedure of 10,000 resamples and a 95% confidence interval. Results showed that self-compassion significantly predicted JoMO (β=0.16, p=0.003), JoMO significantly predicted subjective well-being (β=0.17, p<0.001), the indirect effect of self-compassion on subjective well-being through JoMO was also significant (β=0.03; 95% CI [0.01, 0.05]), while the direct effect remained significant (β=0.72, p < 0.001), indicating partial mediation. These findings indicate that JoMO is one mechanism linking self-compassion and subjective well-being in social media use, although its contribution is relatively small. Practically, the findings emphasize fostering self-compassion and more adaptive social media use to support subjective well-being during emerging adulthood.